New Software Tool for Modelling and Control of Discrete-Event and Hybrid Systems Using Petri Nets - Kučera, Erik; Haffner, Oto; Drahoš, Peter; Cigánek, Ján; Štefanovič, Juraj; Kozák, Štefan (Computing and Informatics, 2020)
The main aim of the proposed paper is to design a new software tool for modelling and control of discrete-event and hybrid systems using Arduino and similar microcontrollers. To accomplish these tasks a new tool called PN2ARDUINO based on Petri nets is proposed which is able to communicate with the microcontroller. Communication with the microcontroller is based on the modified Firmata protocol hence the control algorithm can be implemented on all microcontrollers that support this type of protocol. The developed software tool has been successfully verified in control of laboratory systems. It can also be used for education and research purposes as it offers a graphical environment for designing control algorithms for hybrid and mainly discrete-event systems. The proposed tool can improve education and practice in the field of cyber-physical systems (Industry 4.0).